Causes and Management of Chest Computed Tomography Lesions Progression in Pulmonary Tuberculosis during Antituberculosis Treatment - Shuangyin Yang; Yanmei Feng; Kuiliang Yang; Jie Pu; Pu Wang (International Journal of Mycobacteriology, 2025)
Background: Even with early antituberculosis (TB) treatment, some patients with pulmonary TB (PTB) may experience progression of chest computed tomography (CT) lesions. However, there is limited information on the causes and management of this progression during treatment. This study was undertaken to improve clinical understanding of the various causes and management strategies for the worsening of chest CT lesions in patients with PTB. Methods: A retrospective analysis was performed on the medical records of 61 PTB patients. We evaluated the radiological features, clinical characteristics, laboratory findings, causes, and management of chest CT lesions progression in PTB during anti-TB treatment and compared the characteristics of patients in the paradoxical response (PR) group and the non-PR group. Results: The most common cause of the chest CT progression lesions was PR, accounting for 50.8% (n = 31) of the cases. Other important causes included insufficient anti-TB treatment (21.3%, n = 13), drug-resistant TB (8.2%, n = 5), and comorbidities such as bacterial infections (8.2%, n = 5), fungal infections (6.6%, n = 4), and lung cancer (4.9%, n = 3). Patients with PR were primarily treated by continuing their anti-TB management, whereas those with non-PR due to other causes received treatment targeting the underlying etiology. PR patients were younger (Mann–Whitney U-test, P < 0.001; 95% confidence interval [CI]: 15.8–32.2)., had more asymptomatic cases (74.2% vs. 4.0%; χ2 test, P < 0.001; odds ratio [OR]: 64.3, 95% CI: 12.5–330.2), showed higher Mycobacterium TB culture positivity (64.5% vs. 30.0%; χ2 test, P = 0.015; OR: 4.2, 95% CI: 1.4–12.6), and had quicker lesion progression than the non-PR group (P = 0.004; 95% CI: 1.0–3.0). Conclusion: PR is the major cause of chest CT lesion progression in PTB during anti-TB. Continuation of anti-TB therapy can promote the absorption of lesions. Differences between PR and non-PR patients can help clinicians in diagnosing and guiding treatment strategies.